Pre-employment hearing threshold levels of 59,601 Australian male coal miners compared to an otologically normal international male population (ISO7029:2019). - Liebenberg, Adelle; Nie, Valerie M.; Brichta, Alan M.; Ahmadi, Sima; James, Carole L. (International Journal of Audiology, 2023)
This study compared the pre-employment median hearing threshold level (HTL) distribution from a population of coal miners from New South Wales (NSW), Australia, to an otologically normal, age-matched population described by the International Standards Organisation (ISO) ISO 7029:2019, to determine any differences. This was an observational, retrospective, repeated cross-sectional study. De-identified audiometric records of 59,601 male employees entering NSW coal mining in three representative five-year periods between 1991 and 2015 were utilised. The median HTL deviation of the mining population was statistically significantly different (p < 0.05) from the ISO population, for almost all analyses. Overall, the mining population cohorts have higher (worse) median HTLs compared to the ISO population. The greatest difference occurs at 4 kHz in older age groups, likely indicating noise-induced hearing loss. These findings indicate that some NSW coal mine workers commence their careers with evidence of pre-existing hearing loss (HL), in an industry with excessive noise exposures. These results provide Australian mining and other noisy industries with evidence to support a review of hearing conservation strategies to improve mitigation of hearing loss across the working lifespan. The coal mining industry in Australia typically employs 20,000–30,000 workers annually. These workers are potentially exposed to noise levels between 80 dB(A) and 120 dB(A) whilst at work, and thus at high risk of developing noise induced hearing loss (NIHL). NIHL is the most compensated, occupational disease for coal mining in Australia, costing the Australian State of New South Wales (NSW) up to $4 million each year. And yet: NIHL is entirely preventable. This is the second of two studies of Australian coal mining, analysing a database containing de-identified mandatory audiometric testing results. Evidence of hearing loss within this population was determined in the first study, and the aim of this follow-up study was to determine if there were differences in the median hearing threshold levels in the mining population compared to an otologically normal, international population (ISO7029). The results indicate that the mining population HTLs for males are significantly different (worse) compared to an age and gender matched otologically normal population, specifically at 4 kHz for older workers. Evidence of age-related hearing loss was also found. From a workplace perspective, employers need to consider appropriate workplace interventions to promote hearing loss prevention strategies across the workforce. This information can be used to inform future noise and hearing policies and procedures within this, as well as other noisy industries, to prevent and reduce further exposure of workers to excessive noise.